Penentuan Tinggi Orthometrik Gunung Semeru Berdasarkan Data Survei GPS dan Model Geoid EGM 1996 - Hasanuddin Z. Abidin; Heri Andreas; Dinar Maulana; M. Hendrasto; M. Gamal; Oni K. Suganda (Institute for Research and Community Services (LPPM) ITB, 2004)
Semeru is the highest mountain in Java island with an altitude of about +3676 m above the sea level. This altitude was measured during the Dutch colonial times using the Triangulation method, which is based on angles measurements using a theodolite on the measurement points. At the present times, with the advancement in positioning technology and better knowledge on the Earth's gravity field, an orthometric altitude of a mountain can also be determined by utilizing GPS satellites observation data and a global geopotential model. In this paper, the methodology, mechanism and results of the altitude determination of Semeru mountain using the August 2003 and August 2004 GPS survey data and EGM 1996 geoid model will be described and discussed.The obtained results show that the altitude of Semeru at the present times is about +3677 m above the mean sea level.The paper will be sum up with some closing remarks.